Kajian Partisipasi Masyarakat dan Inovasi Digital dalam Mencegah Penyelewengan Dana Desa di Desa Tirowali: Indonesia - Alisa Alisa; Andika Rusli; Halim Usman (Universitas Muhammadiyah Purwokerto, 2026)
Misappropriation of village funds remains a significant issue in village governance. This study aims to analyze the influence of community participation and digital innovation in preventing the misappropriation of village funds in Tirowali Village. The research employed a quantitative approach using a survey of 90 respondents. The data were analyzed using multiple linear regression after the research instruments were declared valid and reliable. The results indicate that, partially, community participation does not have a significant effect, whereas digital innovation through the utilization of the Village Information System (SID) and Siskeudes has a positive and significant effect. Simultaneously, both variables have a significant effect, as indicated by the Adjusted R² results. These findings emphasize that digital innovation plays a dominant role in enhancing transparency and accountability.